Comparative analysis of rapid test and Enzyme linked Immunosorbent assay for screening of blood donors for Hepatitis B surface Antigen seropositivity (2021)
BACKGROUND: The Hepatitis B surface Antigen (HBsAg) is the most utilized indicator marker of hepatitis B infection. This study assesses the accuracy of the two most common screening assays used to detect HBsAg among blood donors. MATERIALS AND METHODS: A total of 350 eligible blood donors were screened for HBsAg using both Bio-Check HBsAg Rapid screening kit (BioCheck Inc, South San Francisco, USA) and a fourth-generation Enzyme-Linked Immunoassays (ELISA) kit, MonolisaTM HBs Ag Ultra (Bio-Rad Laboratories, Marnes-la-Coquette-France). Questionnaires were used to inquire about risk factors for HBV infection among blood donors. The calculation of sensitivity, specificity, negative predictive and positive predictive values were carried out by comparing the performance of the rapid kit with ELISA test as the reference standard. RESULTS: The prevalence of HBV infection using Rapid Diagnostic Test (RDT) was 5.7% but was 14.6% by ELISA. Using ELISA as a reference, the sensitivity and specificity of RDT were 31.4% and 98.7% respectively. The positive predictive value and negative predictive value for RDT were 80.0% and 89.4% respectively. Overall non-compliance with transfusion-transmitted infection (TIT) risk-related deferral criteria was 38%. CONCLUSION: The low sensitivity of RDT kits precludes its continuous use in high HBV endemic regions where many donors fail to disclose full and truthful information about their risk for TTI. It is suggested that blood banks should complement the use of RDT with a more sensitive assay such as ELISA.